2020
DOI: 10.3390/ijerph17114169
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Novelty Support and Psychological Needs Satisfaction in Physical Education

Abstract: In recent years, novelty has been proposed as a potential fourth basic psychological need. In the present study, the behavior of novelty resulting from support from the Physical Education teacher was evaluated in 723 students with an average age of 13.30 years old. The first objective was to validate the Support for Basic Psychological Needs-4 (SBPN-4) in Physical Education questionnaire, which included support for the novelty factor. The second objective was to test the mediation model in order to confirm the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
2
18
0
8
Order By: Relevance
“…A systematic review and meta-analysis indicates that cooperative learning interventions could be a useful teaching strategy to improve physical education students’ intrinsic motivation [ 100 ]. Research showed that support for novelty can predict satisfaction of basic psychological needs in PE students and positively influence their intrinsic motivation to undertake PA [ 101 ]. Hernández-Andreo et al [ 102 ] proved that the Sports Education model is optimal to improve autonomic motivation in PE students.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis indicates that cooperative learning interventions could be a useful teaching strategy to improve physical education students’ intrinsic motivation [ 100 ]. Research showed that support for novelty can predict satisfaction of basic psychological needs in PE students and positively influence their intrinsic motivation to undertake PA [ 101 ]. Hernández-Andreo et al [ 102 ] proved that the Sports Education model is optimal to improve autonomic motivation in PE students.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, cabe destacar que el estudio del clima interpersonal motivacional se aborda teniendo en cuenta las estrategias de apoyo a todas las necesidades psicológicas básicas y evitando centrarse únicamente en el apoyo a la autonomía, como se viene demandando en la actualidad (Fierro-Suero et al, 2020;Moreno-Murcia et al, 2020;Vasconcellos et al, 2020). De esta forma, además de ver el grado en el que el profesorado apoya o controla cada NPB, se puede calcular el coeficiente CIM, una medida global del clima interpersonal motivacional que puede ser útil en muchos casos (Fierro-Suero et al, 2020).…”
Section: Autonomíaunclassified
“…Por otro lado, cabe destacar que el estudio del clima interpersonal motivacional se aborda teniendo en cuenta las estrategias de apoyo a todas las necesidades psicológicas básicas y evitando centrarse únicamente en el apoyo a la autonomía, como se viene demandando en la actualidad (Fierro-Suero et al, 2020;Moreno-Murcia et al, 2020;Vasconcellos et al, 2020). De esta forma, además de ver el grado en el que el profesorado apoya o controla cada NPB, se puede calcular el coeficiente CIM, una medida global del clima interpersonal motivacional que puede ser útil en muchos casos (Fierro-Suero et al, 2020). Es interesante que los instrumentos aporten información tanto del entorno general creado como de los tipos de estrategias conductuales que el profesorado utiliza (Smith et al, 2016), siendo necesario disponer de medidas objetivas para comprender los comportamientos observables y evaluar así el apoyo social (Vasconcellos et al, 2020).…”
Section: Autonomíaunclassified
See 2 more Smart Citations